2021
DOI: 10.3390/en14227762
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Parameters of Nonlinear Electrical Load

Abstract: The paper deals with issues of modeling nonlinear electrical loads of various types, such an uncontrolled rectifier, thyristor rectifier, thyristor power regulator and mixed equivalent nonlinear load. For these load types, existing analytical expressions were identified to determine the magnitudes of harmonic currents, and waveforms of currents were obtained during measurements in laboratory conditions with variable parameters of the grid impedance and load. The obtained results were compared, and it was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this case, the magnitude values of current sources for different frequencies are set by simplified expressions, where the harmonic current magnitude at the fundamental frequency is divided by the harmonic order. The obtained magnitude values differ significantly from the real measured data [41][42][43]. In this case, the parameters of the energy system and equipment loading are not taken into account.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this case, the magnitude values of current sources for different frequencies are set by simplified expressions, where the harmonic current magnitude at the fundamental frequency is divided by the harmonic order. The obtained magnitude values differ significantly from the real measured data [41][42][43]. In this case, the parameters of the energy system and equipment loading are not taken into account.…”
Section: Introductionmentioning
confidence: 75%
“…To determine the harmonic current magnitude of the nonlinear load, a shunt filter, being virtually a short circuit at a tuned harmonic frequency, is connected to the consumer's buses. In [41], based on experimental studies, it is shown that for a thyristor controlled rectifier, a thyristor power regulator, and a diode uncontrolled rectifier, the relative value of the generated harmonic current to the current at the fundamental frequency remains almost constant before and after connecting the passive filter. It means that the ratio of the current harmonic to the current at the fundamental frequency changes with a small error.…”
Section: Elements Of the Scheme Parameters And Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, wind and solar power generated 22% of the EU's electricity, overtaking gas for the first time [2]. Additionally, in modern industrial power supply systems, there has been a significant increase in the installed capacity of nonlinear electric sources [3], and total capacity in Europe, only in photovoltaics, has increased by 25% from 167.5 GW in 2021 to 208.9 GW 2022 [4]. However, as these sources are integrated into existing electrical grids, complex challenges for power quality appear [5].…”
Section: Introductionmentioning
confidence: 99%